Temperature dependence of twinning stress – Analogy between Cu–Ni–Al and Ni–Mn–Ga shape memory single crystals. Issue 18 (23rd June 2017) - Vronka, Marek; Seiner, Hanus; Heczko, Oleg
Abstract: To obtain a direct non-magnetic analogy to Ni–Mn–Ga 10M martensite with highly mobile twin boundaries, we present the recalculation of twinning systems in Cu–Ni–Al martensite. In this approach, the twinning planes denoted as Type I, Type II and compound have similar orientations for both alloys (Ni–Mn–Ga and Cu–Ni–Al). In Cu–Ni–Al, compound twinning exhibits the twinning stress of 1 to 2 MPa comparable to twining stress of Ni–Mn–Ga. In contrast Type II twinning stress of Cu–Ni–Al is approximately 20 MPa, i.e. much higher than twinning stress for Type II in Ni–Mn–Ga (0.1 to 0.3 MPa). Similarly to Ni–Mn–Ga, the twinning stress of Type II in Cu–Ni–Al is temperature independent. Moreover, no temperature dependence was found also for compound twinning in Cu–Ni–Al.